2017
DOI: 10.1002/ccd.26929
|View full text |Cite
|
Sign up to set email alerts
|

A propensity score matched comparative study between paclitaxel‐coated balloon and everolimus‐eluting stents for the treatment of small coronary vessels

Abstract: The use of paclitaxel-DCB appears to be associated with similar clinical outcomes when compared to second-generation-EES in small coronary artery disease. The findings of this study should be confirmed with larger prospective randomized studies with longer follow-up. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
4
18
0
Order By: Relevance
“…In the current study, Giannini et al tried to challenge this notion again. They wanted to show that the benefits of DCB therapy for treating small vessel CAD remain even when this therapy is compared to the newer second‐generation everolimus‐eluting stents (EESs).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…In the current study, Giannini et al tried to challenge this notion again. They wanted to show that the benefits of DCB therapy for treating small vessel CAD remain even when this therapy is compared to the newer second‐generation everolimus‐eluting stents (EESs).…”
mentioning
confidence: 75%
“…Small vessels with coronary artery disease (CAD) pose a unique problem in the interventional world because of the high incidence of restenosis . Drug‐eluting stents (DESs) have been shown to be superior to bare‐metal stents (BMSs) for the treatment of CAD and are currently the mainstay of therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… TLR: DCB 0% vs. DES/BMS 5%, p N.S. (12 months, 100%) DCB 1.5 months, bailout BMS 6 months, DES 12 months Sinaga et al (2016) [ 25 ] SeQuent Please (2nd/3rd-Gen DES) NR MACE: DCB 11.6% vs. DES 11.7%, p = 1.000 TLR: DCB 5.2% vs. DES 3.7%, p = 0.601 (12 months, 100%) DCB 6 months, DES 12 months Giannini et al (2017) [ 22 ] IN.PACT Falcon (2nd-Gen DES) NR MACE*: DCB 12.2% vs. DES 15.4%, p = 0.538 TLR: DCB 5.6% vs. DES 4.4%, p = 0.720 (12 months, 100%) DCB 1 month, Bailout BMS 3 months, DES 12 months Her et al (2017) [ 27 ] SeQuent Please (1st/2nd Gen DES) NR Pericprocedural MI: DCB 1.9% vs. DES 23.1% p = 0.002 TLR: DCB 1% vs. DES 0%, p = 1.00 (12 months, 100%) DCB 1.5 months, DES 12 months Venetsanos et al (2018) [ 26 ] SeQuent Please, Pantera Lux, IN.PACT Falcon (2nd/3rd-Gen DES) NR TLR: DCB 0.2% vs. DES 1.1%, HR: 1.05; (95% CI 0.72–1.53) TLT: DCB 7.0% vs. DES 6.2%, HR: 0.18 (95% CI 0.04–0.82) (30 months, 100%) DCB 1 month, DES 6 months Single-armed observational studies Unverdorben et al PEPCAD I (2010, 2013) [ 17 , 18 ] SeQuent Please In-Segment LLL: 0.28 ± 0.53 (6 months, 89%) MACE: 15.3% TLR: 11.9% (36 months, 100%) DCB 1 month, bailout BMS 3 months Cuculi et al (2012) [ 44 ] IN.PACT Falcon NR TLR: 4.8% (12 months, 95%) 1.5 months Woehrle et al SeQuent Please World Wide Registry (2012) [ 35 ] SeQuent Please NR …”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Moreover, only a 1st-generation DES was the comparator. Giannini et al showed comparable clinical outcomes in the BELLO DCB group when propensity score matched against patients treated with a 2nd-generation DES (Xience V or Promus) [ 22 ].…”
Section: Patient Characteristicsmentioning
confidence: 99%